Filling the gap: new precise Early Cretaceous radioisotopic ages from the Andes - Aguirre-Urreta, Maria Beatriz (2015)
Two tuffs in the Lower Cretaceous Agrio Formation, Neuquén Basin, provided U–Pb zircon radioisotopic ages of 129.09±0.16 Ma and 127.42±0.15 Ma. Both horizons are well constrained biostratigraphically by ammonites and nannofossils and can be correlated with the ‘standard’ sequence of the Mediterranean Province. The lower horizon is very close to the base of the Upper Hauterivian and the upper horizon to the Hauterivian/Barremian boundary, indicating that the former lies at c. 129.5 Ma and the latter at c. 127 Ma. These new radioisotopic ages fill a gap of over 8 million years in the numerical calibration of the current global Early Cretaceous geological time scale.